'It Can't Really be Answered in an Information Pack…': A Realist Evaluation of a Telephone Housing Options Service for Older People. Issue 3 (15th July 2020) - Harding, Andrew J. E.; Hean, Sarah; Parker, Jonathan; Hemingway, Ann
Abstract : Despite calls for better support to empower people when reassessing their housing in later life, two recent literature reviews highlight a paucity of research on the efficacy of such services. This article reports a qualitative realist evaluation on the efficacy of a UK telephone service providing information on specialist housing to older people. The findings of thirty-one realist interviews with sixteen older people are presented. Information-seekers' existing tenure (social tenant or private owner-occupier/renter) shaped their experience and utilisation of support. Broadly, however, information was considered too 'light touch' to empower older people. However, the widely recognised lack of accessible housing options and reports of non-transparent and unresponsive market practices were also key factors. This study underlines the widely acknowledged need to increase the supply of specialist housing, and recommends that housing options support be reflective of market conditions and be more substantive – including discussion, deliberation, education and advocacy.